Viral Load Supression And Its Associated Factors Among People Living With Hiv In The Ningo Prampram District And Shai Osudoku Hospital - Bransah, M. (University Of Ghana, 2022)
Introduction Institution of the ambitious “90-90-90” strategy by 2020 ( 90% of all HIV-positive individuals will be aware of their status, 90% of those who have been diagnosed with HIV will start and maintain antiretroviral therapy, and 90% of those who are on antiretroviral therapy will have viral suppression) called for robust policies by countries in other to combat HIV/AIDS. The lack of data on the third “90” especially in resource-low Countries is a challenge in the record of this strategy. There is also a lack of regional data in Ghana. In this study, viral suppression among HIV-positive individuals receiving antiretroviral therapy (ART) in a Ghanaian medical facility was evaluated together with the proportion of factors that affect viral suppression. Methodology: A retrospective analysis of secondary data was designed for 479 HIV registrants on highly active antiretroviral therapies for at least six months at the ART Centers in the Ningo Prampram district and Shai Osudoku hospital. Marital status, education, occupation, age, gender and clinic attendance were included in the demographic data. Type of medication and current viral load results were taken from patients’ medical records. The primary outcome, which was divided into viral suppression and viral failure, was viral suppression after six months on ART. In accordance with WHO criteria, viral load suppression (<1000 copies/ml) and viral load failure (≥1000 copies/ml) were used to categorize viral suppression and failure. For the purposes of this study, regular monthly clinic visits for HAART medicine and other clinical treatments throughout the past year were referred to as scheduled clinic attendance. Data analysis was employed using STATA 16/IC 16 software. Summarization of data for categorical variables was done using descriptive statistics. Proportions, means and standard deviation were computed for continuous variables. A significance level of 5% was adopted. Chi Square was used to assess the parameters that contributed to viral load suppression, and logistic regression was used to ascertain how much ART and clinical factors affected viral load suppression. Results: The mean age of the respondents was 41.5  11.5 years. Majority of the PLHIV (61.2%) were within the age group of 30-49 years. Out of the 479 HIV patients, 64.9% achieved viral suppression. Sex (OR=0.63, 95%CI=0.42-0.95), marital status and scheduled visit attendance were significant at the crude level analysis. But only marital status maintained its statistical significance after adjusting with other variables. Compared with individuals who were single PLHIV those who were divorced or separated had 3.5 times the likelihood of having suppressed VL (OR = 3.54, 95%CI = 1.25-10.06). Also, widows were 3 times more likely to achieve VL suppression compared to those who were single. (OR =3.05, 95%CI =0.78 - 12.00). PLHIV who divorced/separated had 3.5 times odds of having suppressed VL compared to the single participants. (OR =3.52, 95%CI = 1.13 -11.00). All other factors were not significantly associated with achieving VL suppression, p<0.05 Conclusion: The proportion of PLHIV in the Ningo Prampram and Shai Osudoku hospital was 64.9%, below the WHO 90% target with suppressed viral load. Marital status was the only sociodemographic factor identified to be associated with viral load suppression. There was no disease-related, ART-related factor affecting viral load suppression. Recommendations: Based on the findings of this study, marital status was a good predictor of VLS and should be highlighted in management policies. Client marital status should be a guide in counselling sessions as a strategy to achieving VLS.Patients who are married should be commended and encouraged to continue to serve as checks for each other. Others who are not married should not be looked down on but counselled on the importance of marital status helping in achieving VLS. In the facility level, married couple living with HIV can be selected as peer educators during counselling sessions with the health staffs to help in educating their peers.
MSc In Clinical Trials
Keywords: Viral Load Supression; HIV; Ningo Prampram District; Shai Osudoku; Hospital